2023
DOI: 10.3390/vaccines11091463
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting COVID-19 Vaccine Acceptance among Pregnant Women: A Cross Sectional Study from Abha City, Saudi Arabia

Asma Saad Habbash,
Aesha Farheen Siddiqui

Abstract: Background: Pregnant women can get infected with COVID-19 with serious sequelae to them and their fetus. Concerns about COVID-19 vaccination safety to mothers and babies, and doubts about its effectiveness, have hindered vaccine acceptance throughout the COVID-19 crisis. The objective of the current investigation was to estimate COVID-19 acceptance rates among pregnant women in Abha city, Aseer region, Saudi Arabia, and determine its clinical and demographic correlates. Method: Descriptive questionnaire-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 71 , 72 Even before the vaccine approval, a multi-national survey conducted in sixteen countries demonstrated that assuming 90% COVID-19 vaccine efficacy the willingness for COVID-19 vaccine was highest among pregnant women from India (>80%) and Mexico, but lower in high-income nations like the USA, Russia, and Australia (45%). 73 Other studies revealed an intention of 37% in Turkey, 74 44.3% in the USA, 75 60.4% in Vietnam, 76 93.7% in Saudi Arabia 77 and 78.5% from India. 65 …”
Section: Discussionmentioning
confidence: 98%
“… 71 , 72 Even before the vaccine approval, a multi-national survey conducted in sixteen countries demonstrated that assuming 90% COVID-19 vaccine efficacy the willingness for COVID-19 vaccine was highest among pregnant women from India (>80%) and Mexico, but lower in high-income nations like the USA, Russia, and Australia (45%). 73 Other studies revealed an intention of 37% in Turkey, 74 44.3% in the USA, 75 60.4% in Vietnam, 76 93.7% in Saudi Arabia 77 and 78.5% from India. 65 …”
Section: Discussionmentioning
confidence: 98%